VARIASI RAGI PADA PEMBUATAN TEMPE KACANG MERAH (Phaseolus Vulgaris. L) - Rinondom AR Mogea; Vanny H Siwi; Rina A Mogea (FMIPA Universitas Papua, 2024)
Red beans can be used as raw material for making tempeh because they contain many nutrients and are also known as a source of vegetable protein and this plant is widely grown in Indonesia. The aim of this research is to look at variations in different yeast dosages and look at fermentation times as well as organoleptic tests for each different yeast dosage in red bean tempe. The results of this study showed no significant difference in the aroma of raw red bean tempe using different amounts of yeast variations. On the other hand, there is a real influence on the color and texture of raw red bean tempe and the taste of fried tempe. This is proven by the asymptotic significance value which has a real influence and shows values ​​that are smaller than 0.05. For the yeast variation preferred by the panelists, the addition of 0.25 gr and for texture, aroma/smell and taste, the panelists chose the 0.50 gr sample because it still smelled of the typical tempe aroma with a savory, sweet and delicious taste. The time needed to make tempe is at time T5, which is 20-25 hours calculated from the time the yeast is added.